2016
DOI: 10.1016/j.exphem.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Cladribine, gemcitabine, busulfan, and SAHA combination as a potential pretransplant conditioning regimen for lymphomas: A preclinical study

Abstract: Hematopoietic stem cell transplantation (HSCT) is an effective treatment for patients with refractory lymphomas. Nucleoside analogues (NA) and DNA alkylating agents are efficacious in treating hematologic malignancies. To design an efficacious and more economical pre-transplant regimen for lymphoma patients, we analyzed the cytotoxicity of cladribine (Clad), gemcitabine (Gem), busulfan (Bu) and suberoylanilide hydroxamic acid (SAHA) in lymphoma cell lines. J45.01 and U937 lymphoma cell lines were exposed to dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…The synergistic effect of the chidamide, cladribine, gemcitabine, and busulfan combination was confirmed in previous research ( 9 ), which found that HDACi combined with CGB synergistically inhibited lymphoma cells in a certain order of medication administration. HDACi increased the sensitivity of genomic DNA to busulfan crosslinking via loosening and opening DNA.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The synergistic effect of the chidamide, cladribine, gemcitabine, and busulfan combination was confirmed in previous research ( 9 ), which found that HDACi combined with CGB synergistically inhibited lymphoma cells in a certain order of medication administration. HDACi increased the sensitivity of genomic DNA to busulfan crosslinking via loosening and opening DNA.…”
Section: Discussionsupporting
confidence: 76%
“…In our previous work, we demonstrated that cladribine, gemcitabine, and busulfan (CGB) had a synergistic effect on killing lymphoma cells, and a histone deacetylase inhibitor (HDACi), vorinostat, sensitized the lymphoma cells to the CGB regimen by causing changes in the chromatin structure ( 9 ). Another HDACi, chidamide, inhibits HDAC 1, 2, 3, and 10 and is an oral agent approved by the National Medical Products Administration (NMPA) of China for refractory/relapsed PTCL, also synergized with CGB in killing lymphoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…SAHA was part of a combination with two antimetabolites, cladribine and Gemcitabine and an alkylating agent, busulfan. This preclinical study in lymphoma cell lines demonstrated that any increase in cytotoxicity could be attributed to stable chromatin relaxation mediated by the antimetabolites and SAHA, thereby increasing the susceptibility of genomic DNA to busulfan alkylation (Ji et al, 2016). SAHA was also used in a multitherapy approach in clinical trials.…”
Section: Hdacis and Multitherapymentioning
confidence: 95%
“…Our previous study has shown that SAHA and cladribine synergistically induce apoptosis in natural killer-large granular lymphocyte leukemia (NK-LGLL) [24]. Cladribine and SAHA, in combination with gemcitabine and busulfan, also provided synergistic cytotoxicity in lymphoma cell lines [25]. Stephen E. Spurgeon showed a phase 1/2 study, which using SAHA, cladribine, and rituximab in relapsed B-cell non-Hodgkin lymphoma (NHL) and previously untreated MCL resulted in a high complete response rate [26].…”
Section: Ivyspringmentioning
confidence: 99%